(untitled) (The Research of Medical Science Review, 2025)
Background: The stomach epithelium is colonised by gram-negative spiral-shaped Helicobacter pylori. Chronic gastritis, ulcers, adenocarcinoma, and gastric mucosa-associated lymphoid tissue lymphoma are linked to Pylori infection. Basic H&E stain can detect it. The particular method of immunohistochemistry is reliable for H. pylori diagnosis. Previous research had mixed outcomes. This research was done to gather local demographic data. Objective: To ascertain the diagnostic precision of immunohistochemistry in identifying Helicobacter pylori infection in stomach samples obtained in the histopathology department using H&E as the gold standard. Study Design: Cross Sectional Study Study place and duration: Department of Pathology, Sir Ganga Ram Hospital, Lahore from 21- 6-2024 to 21-12-2024. Patients and methodology: 260 samples were received from gastroenterology department and were divided in two parts. On one part, immunohistochemistry was applied and findings were recorded. On second part, H&E was applied and findings were recorded. All the data was recorded in proforma while later on analyzed in SPSS 20.0. Results: Patients in this research ranged in age from 16 to 75 years, with a mean age of 41.73 ± 16.64 years. The male-to-female ratio was 1:2.25, with 80 (30.8%) male and 180 (69.2%) female patients. The immunohistochemical test for H. pylori infection has 85.2% sensitivity, 100% specificity, 100% PPV, 93.7% NPV, and 95.4% diagnostic accuracy. Conclusion: Thus, immunohistochemistry is found to be reliable enough to detect H. pylori infection in gastric biopsies.